Deconstructing learning spaces: applying derrida's theory in the design of higher education buildings - Indrayuni, ST.,MT, Armi; Syamsu A. Kamaruddin; Arlin Adam (Jurnal Info Sains : Informatika dan Sains, 2024)
This study aims to analyze and apply Jacques Derrida's concept of deconstruction in the context of higher education architectural design. The primary focus is on creating learning environments that not only support diversity in learning methods but also foster spaces that stimulate creativity and dynamic interaction among students. The research seeks to explore how deconstructivist principles can be implemented in modern learning space design, distinguishing it from more conventional modern architectural principles. The methodology includes a detailed comparative analysis between modern and deconstructivist architecture, critically assessing aspects such as design philosophy, space utilization, aesthetics, and the socio-cultural impact of both architectural approaches. Furthermore, the study employs experimental design, where various deconstructivist concepts are tested in learning space design, including through 3D modeling and digital simulations, to explore their potential in a real educational setting.The results reveal striking differences between deconstructivist and modern architectural approaches. Deconstructivist architecture tends to use asymmetrical forms, complex structures, and varied interpretations, in contrast to the focus on functionality, symmetry, and efficiency often found in modern architecture. The conclusion is that deconstructivist architecture, with its principles of challenging norms and exploring the potential of form and space, can significantly contribute to creating rich and stimulating learning environments. This approach not only enriches the aesthetic aspects of educational environments but also encourages critical thinking, innovation, and creativity among students.